INCLUSIVE EDUCATION ACCORDING TO ABDUL MU'TI - Alban, Alban (Universitas Islam Negeri Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2024)
Inclusive education is an approach that integrates children with special needs into the general educational environment without sacrificing their individual needs. This study aims to determine the views on inclusive education according to Abdul Mu'ti. The method used in this study is the library research method with a semiotic approach. The results of this study regarding Abdul Mu'ti's views on inclusive education show the importance of equal access to quality education for all children, regardless of their background or physical condition. This concept not only emphasizes physical integration, but also supports appropriate individual support, collaboration between all stakeholders, and a differential learning approach. By using these principles, inclusive education according to Abdul Mu'ti aims to create an inclusive learning environment, supporting, and stimulating the holistic development of each child, thus preparing them to actively participate in a socially and academically diverse society. In conclusion, through effective inclusive education, we open the door for all children to reach their full potential and build a better future for all generations.